Modification of the RLA model for presenting a cluster system of a composite material with a fractal filler structure - A. V. Belko; N. N. Babarika; I. S. Zeylikovich; A. V. Nikitin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper proposes a modification of the diffusion-limited aggregation model to study the properties of a cluster system. A computational experiment to determine the mutual influence of the sticking probability and the volume concentration of particles on the formation of fractal clusters in a cluster system was carried out in accordance  with  the  second-order  orthogonal  central  compositional  plan  (OCCP).  As  a  result of a computational experiment in accordance with the OCCP, an equation was obtained for the dependence of the mass fractal dimension of clusters on the volume of particle concentration and the probability of adhesion of diffusing particles and cluster particles in the adhesion zone. This dependence was obtained in a range of volume concentration of particles from 2 to 5 % and the probability of adhesion of diffusing particles and particles of clusters in the adhesion zone from 0.2 to 1.